(untitled) - Horstmann, Cay S. (New York, 1998)
This unique book teaches you the fundamental concepts of good computer programming while introducing you to one of the most powerful languages in use today—Java! It gives you an ideal balance between programming concepts and the details of Java. Rather than exhaustively cover the entire language, the author focuses on a subset of Java—a lean and practical core that is manageable, yet detailed enough to create powerful Java applets. And as you master the basics of Java, you'll be developing solid programming skills that will increase your effectiveness no matter which language you work with! Includes a wealth of practical advice, tips, and reference material.
Keywords: Xử lý dữ liệu điện tử,Electronic data processing